Comparing Handheld Meters and Electronic Dosimeters for Measuring Ultraviolet Levels under Shade and in the Sun. (20th January 2016) - Dobbinson, Suzanne; Niven, Philippa; Buller, David; Allen, Martin; Gies, Peter; Warne, Charles
Abstract: This study aimed to compare the validity, reliability and practicality of alternative portable methods for measuring erythemal UVR levels in passive recreation areas in public parks. UVR levels were measured for point in time comparisons between Solarmeter 6.5 handheld meters and time‐stamped electronic dosimeters in a large central park in Melbourne, Australia. Observations were made at 20 locations in the park by two research assistants under two conditions: (1) matched shade (2) contrasting shade—no shade. Comparisons were also made with scientific instruments on the UVR monitoring station rooftop and by remotely selecting UV records and forecasts on cloud‐free dates of park observations. There was good agreement between the portable UVR instruments in the park setting as confirmed via Bland Altman plots, while the dosimeter appeared less sensitive to change in shade conditions. The rooftop measurements showed that the Solarmeter 6.5 UVR readings were comparable to those of the adjacent rooftop instruments. The practicalities of using the dosimeters and Solarmeters for behavioral studies are discussed. These findings provide a basis for use of the Solarmeter 6.5 to measure changes in UVR levels due to different environmental conditions with relative accuracy for intervention studies in outdoor settings. Abstract : Comparisons of UV measurements and other practical information are provided to assist public health researchers with choice of portable radiometers for future studies.